Diversificação e evolução fenotípica em peixes cascudos (Siluriformes: Loricariidae: Loricariinae) - Souza, Laura Barreto de Paula (2018)
One of the major causes of the phylogenetic, temporal and spatial variation of species richness is attributed to the processes of differential speciation and extinction of lineages, named diversification. There is also a great phenotypic diversity among species that may be related to diversification. The development of phylogenetic comparative methods allowed the study of the diversification and evolution of species traits. The aim of this study is to investigate the pattern of diversification and trait evolution of the suckermouth armored catfish, Loricariinae subfamily, and to investigate if these attributes are related to the diversification rates within the clade. We used a phylogeny containing 114 representatives of subfamily species and their attributes body size, climatic niche and microhabitat (substrate) - position and width for both - to evaluate the evolutionary rates and test the relationship between these different axes of the species niche and their evolutionary rates. We estimated diversification rates with BAMM and performed phylogenetic correlation analyzes (STRAPP) to address the question of whether the attributes are related to the diversification process in the subfamily. We also performed analyzes of disparity through time (DTT) to explore the temporal pattern of phenotypic evolution. The diversification analysis showed that the subfamily had high rates of diversification. Body size presented heterogeneous rates among clades, presenting a shift of diversification in which the specie Paraloricaria agastor had the smallest size of the clade. Climatic niche position presented a heterogeneous pattern of diversification rates, with a shift involving six species of Rineloricaria that retained their niche position. Diversification of the climatic niche width revealed the most heterogeneous pattern, presenting four shifts occurring in clades in which some species possessed greater climatic niche widths. However, the rates of diversification of both micro-habitat position and width did not show any shift. The STRAPP test revealed no correlation between any of the traits studied with diversification, showing that evolutionary process of Loricariinae seems to be independent of the phenotypic attributes investigated. The DTT revealed that in most of the Loricariinae’s evolutionary history, the averages of disparity of the studied attributes evolved under neutral evolution, although they presented peaks of phenotypic disparity within the clades in the most recent time. The results showed that Loricarinae evolved through a non-adaptive radiation where vicariant events would have promoted allopatric speciation and the high diversification rates. In fact, it is known that the radiation of Neotropical fishes was closely related to geological processes of basin formation (hydrogeological hypothesis). DTTs analyzes reinforces this claim, because in most of the evolutionary history the attributes evolved neutrally, without association with diversification, as expected in non-adaptive radiation. Although the subfamily evolved under non-adaptive radiation, divergent selection processes possibly occurred in species independently, promoting significant disparity of attributes within the clades at the present time. The results obtained highlights a peculiar evolutionary history for Loricariinae and a unique known example of nonadaptive radiation for the Neotropics, which can be enlighten the understanding of the yet little known processes that led to the extraordinary diversification of the Neotropical fishes.